Research on Marketing Strategy of Huawei Brand in Kazakhstan - Baituk Raushan (International Journal of Engineering and Management Research, 2019)
Marketing research is a complex multi-step process that requires in-depth knowledge of the object of study, the accuracy and timeliness of the results of which largely determine the successful operation of the entire enterprise. Most business failures (from loss of market share to bankruptcy) are because important strategic decisions are made either in conditions of lack of information or on the basis of erroneous or outdated data. Marketing research will provide the necessary information and reduce the risk when making important decisions. Marketing strategy is the collection of information about the activities of the enterprise, in the main areas (product, price, customers, and promotion) and the use of the results to choose the direction of business development. The goal is to identify possible ways to improve the effectiveness of Huawei’s marketing strategy in Kazakhstan. Theoretical issues of marketing are considered, namely the concept of marketing, goals, objectives, functions and issues of marketing, marketing macro and microenvironment, marketing research. This article will be of positive importance for the study of foreign investment of Chinese enterprises.